Insights into the constellating drivers of satiety impacting dietary patterns and lifestyle - Rakha, Allah; Mehak, Fakiha; Shabbir, Muhammad Asim; Arslan, Muhammad; Ranjha, Muhammad Modassar Ali Nawaz; Ahmed, Waqar; Socol, Claudia Terezia; Rusu, Alexandru Vasile; Hassoun, Abdo; Aadil, Rana Muhammad (Frontiers in Nutrition, 2022)
Food intake and body weight regulation are of special interest for meeting today’s lifestyle essential requirements. Since balanced energy intake and expenditure are crucial for healthy living, the physiological mechanisms of human body encode complex and not yet fully understood mechanisms as satiety and satiation involved in appetite control. This work aim to explore and to compile the main factors influencing food efficiency of satiating by updating recent knowledge to point out maybe new perspectives of the potential drivers of satiety interfering food intake regulation. Besides, the external factors impacting satiety efficiency are highlight-ed. Based on mechanisms related to food consumption and dietary patterns several physical, physiological, and psychological factors affect satiety or satiation. Gut signals enable endocrine mechanisms targeting brain, in response to food intake and other behavioral stimuli, such signaling pathways inducing satiety. Moreover, complex food composition and structures result in considerable variation in satiety responses for different food groups and their quality. A better understanding of foods and factors impacting the efficiency of satiety could be helpful in making smart food and dietary recommendations and choices showing health benefits, based on updated scientific evidence.